Peran Kepemimpinan Transformasional Kepala Sekolah Dan Motivasi Kerja Dalam Membentuk Kedisiplinan Guru Melalui Komitmen Organisasi - Nurhasanah Nurhasanah; Ramdan Ramdan; Atikah Atikah; Mela Pebriana Sari; Siti Laela (Universitas Pakuan, 2026)
THE ROLE OF TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPALS AND WORK MOTIVATION IN SHAPING TEACHER DISCIPLINE THROUGH ORGANIZATIONAL COMMITMENT Abstract This study aims to analyze the role of principals' transformational leadership and work motivation in shaping teacher discipline through organizational commitment. The research focuses on how transformational leadership, work motivation, and organizational commitment integratively shape teacher discipline as a form of professional awareness, not merely administrative compliance. The research employs a qualitative approach with a descriptive-analytical design, utilizing library research methods. Data were gathered from academic journals and scholarly books relevant to the research focus. Data analysis was conducted using content analysis and thematic synthesis to identify patterns of relationships between variables in an integrative manner. The findings indicate that principals' transformational leadership acts as a primary catalyst in enhancing teachers' intrinsic motivation through shared vision, role modeling, intellectual stimulation, and individualized consideration. A strong sense of work motivation subsequently reinforces organizational commitment, particularly affective and normative commitment, which functions as an internal mechanism in fostering voluntary and sustainable teacher discipline. Discipline does not emerge as a direct consequence of administrative control but rather as a result of the internalization of values and emotional attachment to the school. Improving teacher discipline necessitates integrative leadership practices that strengthen both motivation and organizational commitment, allowing discipline to develop as sustainable professional awareness. This research recommends strengthening principals' capacity to implement transformational leadership, enhancing motivating professional development programs, and creating a school culture that fosters a sense of belonging and teacher commitment.